A comparative assessment of proximate and elemental composition six weedy grasses for their potential use as fodder - Khan, Raees; Khan, Muhammad Nauman; Ullah, Hadayat; Basit, Abdul; Razzaq, Abdur; Ahmad, Mushtaq; Zafar, Muhammad; Kilic, Omer; Ozdemir, Fethi Ahmet (Progress in Nutrition, 2018)
In the current study six weedy grasses samples; Alopecurus myosuroides, Brachiaria ramosa, Chrysopogon aucheri, Phalaris minor, Pennisetum orientale and Stipa capensis were collected and evaluated for their potential use as fodder. These species were analyzed for their proximate and mineral composition in three phenological stages. A total of ten elements (Ca, Na, Si, S, Cu, K, Al, Mg, Cl and Fe) that are vital for proper development, health and to produce milk, were detected in varied contents from species to species and phenological stages. Minerals content were mostly detected maximum at reproductive and post-reproductive stages. All six species were also a good and valuable source of nutrients (NDFs, ADFs, ADLs, cellulose and hemicellulose). All species had low moisture and high dry matter contents. Ash contents were high in pre-reproductive stages. Stipa capensis has highest nitrogen (57.96%) contents in pre-reproductive stage in all studied grasses. All the assessed species in the light of current findings (minerals and proximate composition) shows that they are a good potential source of fodder for cattles and will be very helpful to fulfill the current crisis of fodder.